Kant’s ethical argument in Russian religious thought: Solovyov, Chicherin, Tolstoy, Novgorodtsev - Konstantin Antonov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия)
The author asks the question about the meaningfulness of the substantive and stylistic opposition of Kant to Russian religious thinkers, which has become commonplace in the research literature. As an empirical test of this opposition, the paper attempts to reconstruct the discussion related to the reception of Kantian ethics in Russian religious thought of the last quarter of the 19th - early 20th century. The author offers his explication of the Kantian ethical argument and examines its perception by the major Russian religious thinkers of the period: V.S. Solovyov, B.N. Chicherin, L.N. Tolstoy and P.I. Novgorodtsev, and reconstructs the polemics between them. It demonstrates how each of them builds his own logic of relation of the ethical to the religious, legal and political, in one way or another relying on the Kantian argument and or incorporating it into his own train of thought. The idea of the moral autonomy of the subject is harmoniously regarded by all authors as the main achievement of Kant’s ethics, and the suspicion of its explicit or implicit abolition is one of the central points of polemics between them. The author believes that this conclusion falsifies the notion that Russian religious thought and Kantianism are incompatible. Finally, the dialectic of the justification of autonomy and the fear of its loss is described as one of the driving forces of Russian religious philosophy, which forced its representatives to seek and design new forms of religious and socio-political life and thought.